The Impact of family planning practice on neonatal mortality - Baltazar, Jane C. Caceres (1984.)
The causal association of previous family planning practice and neonatal mortality was investigated in a case-control study comparing 125 neonatal deaths with two sets of 122 controls, one being health provider-based the other being neighborhood-based. Using the health provider-based control group for comparison, the odds ratio of neonatal mortality among children whose mothers reported previous family planning practice was 1.02 (0.62 to 1.69, 95% confidence limits); using the neighborhood control group for comparison, the odds ratio was 0.84 (0.51 to 1.39, 95% confidence limits). When effective methods of contrception were used for at least five years, the relative odds of noenataldeaths was less than 1.0, indicating a protective effect (OR=0.39 for case-health provider-based comparison, and OR = 0.60 for case-neighborhood control comparison). However, these odds ratios were based only on very small numbers. The most probable sources of bias in this investigation are discussed. Of the different sources, misclassification of exposure may have produced the most bias in the overall association, the bias being towards the direction of lowering the preventive effect of exposure and even making it appear as a weak risk factor. Because the study size was relatively small, because several sources of bias could exist in a study of this nature, and because there have been no other published investigations to support the family planning-neonatal mortality hypothesis, further research is needed to determine whether the previous practice of family planning by the mother is causally associated with a reduction in the risk if neonatal mortality in the offspring. JANE CACERES-BALTAZAR
Thesis (Doctor of Public Health)--University of California, Los Angeles
Keywords: Family planning; Birth control; Newborn infants -- Mortality